Laparoscopic Assisted Vaginal Hysterectomy: A Case Control Comparative Study with Total Abdominal Hysterectomy (Faridpur Medical College Journal, 2014)
This case control study was conducted in the department of Gynae & Obstetrics, Sir Salimullah Medical College & Mitford Hospital (SSMC & MH), Dhaka, during the period of January 2008 to December 2008 to compare the length of operation, blood loss, length of hospital stay, drug requirements for pain and post-operative pain and activity levels between Laparoscopically Assisted Vaginal Hysterectomy (LAVH) & Total Abdominal Hysterectomy (TAH). A total of 50 patients who met some eligibility criteria were consecutively included in the study and matched in a case control manner for age, weight, diagnosis & uterine size. The procedures were performed by the same surgeon. On average, LAVH operations took significantly longer than TAH operations (P